Noise Analysis Around Jababeka – Cikarang Industrial Area - Yuliana, Yuliana; Fianti, Fianti (Universitas Negeri Semarang, 2024)
Noise is an unwanted sound from a business or activity at a certain level and at a particular time that can cause disturbances to human health and environmental comfort. Noise can cause psychological and physiological impacts. The Ind is one of the largest industrial areas in Bekasi Regency, West Java. This study aims to analyse the noise levels around the industrial area of Jababeka-Cikarang. This type of research is survey research with a quantitative approach. This study measures the sound intensity level in the Jababeka–Cikarang area, up to a distance of 20 km from the Jababeka – Cikarang area. Data analysis used descriptive analysis in the form of graphs. The study results show that the noise level in the Jababeka-Cikarang area exceeds the threshold set by the Threshold, which is 70 dB to 85 dB.